A Prelude to the Boko Haram Insurgency: A Doctrinal Interrogation - W. A. Duyile (Britain International for Academic Research (BIAR) Publisher, 2023)
This study looked at Northern Nigeria prior to the origination of Boko Haram in the 21st Century. The research also traced the activities of Islamic sects from the 19th century and the factors that preluded the Boko Haram war. A retrospect and review of the facts was made, in order that scholars would have an insight on the doctrinal influences of sect activities on clandestine groups like Boko Haram. The research examined the perceptions, as well as doctrines, philosophy and influence. The study relied on documentary data. The documentary data were sourced from newspapers, journal papers, internet sources and correspondence. The documentary was subjected to internal and external criticism for authentication, and then to textual and contextual analyses. This crisis in Northern Nigeria correlates very much to the sectarian interpretations. The undefined Nigerian border with Cameroon, Chad, and Niger in the North allowed for interaction among the people of both nations. It is this lacuna that made Boko Haram evasive in strategic terms. It is also the core reason for insecurity and terrorism.